OPTIMASI CARBOPOL 940 DAN GLISERIN PADA GEL TANAMAN ANTING-ANTING (Acalypha indica L.) SEBAGAI ANTIOKSIDAN - prayoga fery yuniarto (Jurnal Inovasi Farmasi Indonesia (JAFI), 2020)
Acalypha indica L. is suspected has an antioxidant. The use of anting-anting directly considered less practical, so that it made the gel preparations. And then it use optimation by Simplex Lattice Design method so get the most optimum antioxidant gel. This research purpose for know the efficacy of apple optimation gel as an antioxidant. Maceration extract made of gel with components carbopol 940(A) and glycerin(B) so that get three formulas, F1 (100%A), F2 (50%A, 50%B), dan F3 (100%B) and then optimation by viscosity, adhesion, and dispersive power. Simplex Lattice Design method with use program design- expert 8.0.6.1. Research antioxidant activity of optimum gel by method of DPPH. Antioxidant activity calculated by λ maximum and operating time so that get IC50 values by probit analysis. Optimation mixture between carbopol 940 and gliserin as components is carbopol 1,18 and glycerin 3,82. The resulted of t-test of viscosity, adhesion, and dispersive power showed no significant difference between the predictions with actual experimental result. The result showed optimum gel of apple fruit has antioxidant activity amounted to 164,58 ppm.